Advanced security and privacy technique for digital text in smart grid communications. (July 2021) - Khadam, Umair; Iqbal, Muhammad Munwar; Saeed, Saqib; Dar, Saadat Hanif; Ahmad, Awais; Ahmad, Mudassar
Abstract: In the current era of technology, digital contents copyright protection is a significant issue in the Internet of Things and smart grid. Digital contents are distributed, reproduced, and disclosed with extensive use of communication technologies such as the cloud. It has become quite easy to produce an illegal copy of digital content. Limited techniques are available for text documents ownership verification and copyright protection in the Internet of Things. However, most of the existing techniques produce distortion during watermark insertion, which directly impacts imperceptibility. We propose a robust and secure digital text watermarking technique for Microsoft Word documents in the said perspective. The watermark is extracted with high probability, which illustrates that the proposed technique is robust, imperceptible, and improves the capacity. The results of the proposed technique are compared with the previous techniques of text watermarking. The proposed technique is imperceptible with the Peak signal-to-noise ratio is 33.65, and the similarity percentage is 99.42%. The length of the secret message is improved from 0.2 to 1.24 kilobytes. Graphical abstract: Figure 1. Methodology for text document copyright protection Image, graphical abstract